Modeling and simulation of modal analysis-based technique on UTP distribution network for evaluating harmonic resonances - Hasan, K.N.M. (Asian Research Publishing Network, 2015)
Harmonic resonance is one of main concern when dealing with harmonic in an electrical network. Its presence is most likely to cause amplification of harmonics distortion in the system. Numerous techniques had been deployed to reduce the effects of harmonic resonance in power network. Installation of harmonic filters is a common and cheaper solution. However, it is difficult to identify optimum location to install harmonic filter and there is no particular method that can assist the decision. Modal Analysis-based technique was proposed in evaluating resonance in additional to commonly used frequency-scan technique. In modal approach, further evaluation on finding participating factor and sensitivity analysis was carried out to evaluate resonance in the system. In this paper, harmonic resonance mode analysis (HRMA) is presented and evaluated when implemented on several standard test systems including standard IEEE 14-Bus System. It was then implemented on the new academic building network of Universiti Teknologi Petronas (UTP) electrical network. The load flow of the whole network was obtained prior to that to ensure the reliability of data used for HRMA analysis. The frequency scan result was also obtained for the same network. The HRMA plots were compared to the frequency scan results for verification. Sensitivity evaluation in HRMA technique was carried out to determine participation factor of each buses in the network. From these results, HRMA technique was proven to be reliable and provides a simpler way to evaluate the existence of resonance in the system and at the same time indicates which buses are more dominant to a particular resonance. This provides some basis in assisting personnel to decide on the location to mitigate the resonance and it can be used in complement to the frequency scan technique. Â© 2006-2015 Asian Research Publishing Network (ARPN).